2020
DOI: 10.3390/pharmaceutics12070639
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability and Degradation Pathways of Venetoclax under Stress Conditions

Abstract: Venetoclax is an orally bioavailable, B-cell lymphoma-2 (BCL-2) selective inhibitor, used for the treatment of various types of blood cancers, such as chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL). In this study we investigated the degradation of venetoclax under various stress conditions including acidic, basic, oxidative, photolytic and thermolytic conditions. We isolated and identified six of its main degradation products produced in forced degradation studies. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…If the fingerprint region of S=O vibrations between 1000-500 cm -1 is [32] examined, it is noteworthy that Venetoclax and Navitoclax dissolved in DMSO and DMSO have similar peaks (Figure 2). When the FTIR spectrum of powder Venetoclax was examined, it was detected there were similar peaks to Venetoclax dissolved in S3 in the 1600-600 cm -1 range and the orientation of the whole spectrum curve was also similar [33].…”
Section: Resultsmentioning
confidence: 99%
“…If the fingerprint region of S=O vibrations between 1000-500 cm -1 is [32] examined, it is noteworthy that Venetoclax and Navitoclax dissolved in DMSO and DMSO have similar peaks (Figure 2). When the FTIR spectrum of powder Venetoclax was examined, it was detected there were similar peaks to Venetoclax dissolved in S3 in the 1600-600 cm -1 range and the orientation of the whole spectrum curve was also similar [33].…”
Section: Resultsmentioning
confidence: 99%
“…The degradative pathways can be determined based on fragmentation patterns that are observed. After determination of degradant pathways, structure elucidations of degradants are done by synthesizing or isolating methods and further characterized by employing LC-MS, LC-UV, and LC-NMR techniques [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Characterisation Of Degradants By Lc-msmentioning
confidence: 99%
“…In our previous studies on the stability and liquid chromatography analytical method development for venetoclax, we observed that venetoclax formed crystals after a few days from some of the solvents used for the dissolution of venetoclax [59,60]. Therefore, we performed a targeted crystallization experiment from the most promising solvent system identified in our previous study [60].…”
Section: Preparation Of Venetoclax Hydratementioning
confidence: 99%